Tanzpraxis in der Forschung - Tanz als Forschungspraxis Choreographie, Improvisation, Exploration. Jahrbuch TanzForschung 2016 - Quinten, Susanne; Schroedter, Stephanie (Tanzforschung, 2018)
Dance practice is gaining just as much in importance in research as it is becoming a kind of research in itself. Choreography, improvisation and exploration are expanding conventional discursive methods of knowledge generation and transfer to incorporate aesthetic dimensions of movement, corporeality, sensuality and emotion. This volume, with its interdisciplinary structure, provides an insight into the multi-faceted trend of research approaches that have either developed directly from, or refer back to, dance practice. Using projects as concrete examples, the contributions in this volume present theoretical and methodological foundations and historical connections advances in knowledge.